Frequency of different histological types of lung cancer in core needle biopsies in a clinical-surgical pathology laboratory in Rosario in the period 2016-2021 - Bertaina, María del Rosario; Chiesa, Dr. Hernán; Damiano, Dr. Mario (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Lung cancer is one of the most frequent cancers nowadays worldwide. Different histological types can be observed, the most frequent being adenocarcinoma, non-small cell carcinoma and, thirdly, small cell and squamous cell carcinoma. Objective: to calculate the frequency of histological types of lung cancer in biopsies of patients older than 18 years analyzed in an anatomic pathology laboratory in Rosario in the period 2016-2021. Materials and Methods: a quantitative, descriptive, observational, cross-sectional, retrospective, descriptive study was carried out from the analysis of biopsy reports of lung nodular lesions. Results: 197 biopsies of pulmonary nodular lesions were analyzed. 132 reports indicated the presence of neoplastic cells. The highest frequency was in the range of 60-69 years. The 60.9% of the patients were male. The most frequent histologic type was adenocarcinoma NOS (30%), followed by non-small cell undifferentiated carcinoma (16%) and small cell (10%) and squamous cell (10%) carcinoma. Biopsy specimens were representative in 86% of cases. Conclusions: the most frequent histologic type in the present series was adenocarcinoma NOS, with a higher frequency between 60-69 years in the male sex, as reported in the international literature